ANALYZING FACTORS AFFECTING STOCK PRICE MOVEMENT OF BANKING SECTOR IN INDONESIA STOCK EXCHANGE - Angkouw, Karina Roseline; Pangemanan, Sifrid S.; Pandowo, Merinda . (FEB Universitas Sam Ratulangi Manado, 2018)
Abstract: The stock market is all about dynamics and that is why investors and fund managers have always been confronted with the problem of accurately predicting the stock prices so as to earn decent returns. Investment in shares offers the benefit of liquidity as well as the opportunity to beat the market and earn high returns. However, the task of predicting share prices is far from simple. Share price movement is not independent in nature and both intrinsic, as well as extrinsic factors, have been established to exercise influence over stock price movements. The purpose of this research is to analyze factors influencing stock price of the banking sector in the Indonesian Stock Exchange index. The objects of this research are banking stocks that are listed in Indonesia Stock Exchange. This research is an explorative study and uses a quantitative method which utilizes technical analysis and t-test as the tool of analysis. The research results show that the upward movement of banking stocks happened in the year 2008 and the factor influencing this movement is the increase in interest rate announcement by Bank Indonesia. Recommendation derived from this research is for investors and fund managers to give more attention towards announcement and interest rate of a sector in the country in their investment portfolio.Keywords: stock price, interest rate, political effects, economic effects